Molecular Diagnosis Of Tuberculosis and Non-Tuberculous Mycobacteria: Evaluating Dual PCR Targeting IS6110 and rpoB Gene - Soni, Ashish; Sharma, Indu; Soren, Swati; Shaji, Jasna; Ambiga, Darshan; Shindhe, Diksha; Kukreti, Anjali; Saini, Anushka; Sharma, Narotam; Singh, Ajay; Singh, Ankita; Singh, Jagjeet (Journal of Neonatal Surgery, 2025)
A sum of 100 clinical specimens was examined, showing that sputum had the highest positivity rates for MTB, with 13 of 34 samples testing positive for rpoB and 9 for IS6110. Significantly, differences among these markers were noted, indicating possible genetic variations or co-infections. Pus samples (n=26) demonstrated a low detection rate, with merely 6 samples testing positive for IS6110, while fistula samples (n=18) exhibited an equal distribution of rpoB and IS6110 positivity (7 cases each). Menstrual blood samples (n=9) presented distinct diagnostic challenges, showing rpoB positivity in 2 instances and IS6110 in 3 instances. In total, MTB was detected in 35 instances (70%), whereas NTM was verified in 15 instances (30%). These results highlight the importance of multi-gene molecular diagnostics for accurate distinction between MTB and NTM, decreasing the chances of misdiagnosis. The research shows that dual PCR is a strong and dependable diagnostic method, potentially enhancing TB case identification and focused treatment approaches. Additional validation involving varied populations and incorporation with next-generation sequencing is advised to improve diagnostic precision and public health strategies.